Consumption trends of white cassava and consumer perceptions of yellow cassava in Ghana - Duah, E.A.; Parkes, Elizabeth Y.; Baah, R.O.; Acquatey-Mensah, A.; Danquah, A.O.; Kirscht, P.; Kulakow, Peter A.; Steiner-Asiedu, M. (Science and Education Publishing Co., Ltd., 2016)
Vitamin A deficiency has been one of the major nutritional problems for many countries where cassava is eaten as a major source of energy. In an attempt to help reduce the incidence of vitamin A deficiency, bio-fortified cassava which contains more pro-vitamin A carotenoids than the white cassava, has been introduced to such areas. This study therefore endeavored to find out how often Ghanaians ate cassava and its products, as well as what Ghanaian consumers knew about bio-fortified cassava and their willingness to consume it. A survey was done between the month of January and March using 287 participants in the Greater Accra Region of Ghana which gathered information on their demographics, and their frequencies of the consumption of cassava and its products. Data on the knowledge of the participants on yellow flesh cassava, and their willingness to accept it were also gathered. Logistic regression was used to determine the relationship between some demographic characteristics and knowledge and ‘willingness-to-accept’ biofortified cassava. The cassava product which was mostly consumed by the participants was gari. Sixty-three percent of the participants had no knowledge of bio-fortified cassava. About half of them were willing to accept the biofortified cassava, and more than half of the participants perceived that yellow cassava could be used for some white cassava products. Providing nutritional information and sensitizing consumers on the benefits of biofortified cassava can enhance its consumption in Ghana.